I stay at home with headache. A survey to investigate how the lockdown for COVID-19 impacted on headache in Italian children. (November 2020) - Papetti, Laura; Loro, Pierfrancesco Alaimo Di; Tarantino, Samuela; Grazzi, Licia; Guidetti, Vincenzo; Parisi, Pasquale; Raieli, Vincenzo; Sciruicchio, Vittorio; Termine, Cristiano; Toldo, Irene; Tozzi, Elisabetta; Verdecchia, Paola; et al.
Objective: The present Italian multicenter study aimed at investigating whether the course of primary headache disorders in children and adolescents was changed during the lockdown necessary to contain the COVID-19 emergency in Italy. Methods: During the lockdown, we submitted an online questionnaire to patients already diagnosed with primary headache disorders. Questions explored the course of headache, daily habits, psychological factors related to COVID-19, general mood and school stress. Answers were transformed into data for statistical analysis. Through a bivariate analysis, the main variables affecting the subjective trend of headache, and intensity and frequency of the attacks were selected. The significant variables were then used for the multivariate analysis. Results: We collected the answers of 707 patients. In the multivariate analysis, we found that reduction of school effort and anxiety was the main factor explaining the improvement in the subjective trend of headache and the intensity and frequency of the attacks ( p  < 0.001). The greater the severity of headache, the larger was the clinical improvement ( p  < 0.001). Disease duration was negatively associated with the improvement ( p  < 0.001). It is noteworthy that clinical improvement was independent of prophylaxis ( p  > 0.05), presence of chronic headache disorders ( p  > 0.05) and geographical area ( p  > 0.05). Conclusions: Our study showed that lifestyle modification represents the main factor impacting the course of primary headache disorders in children and adolescents. In particular, reduction in school-related stress during the lockdown was the main factor explaining the general headache improvement in our population.